2021
DOI: 10.3389/fnut.2021.771518
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Salvia Supplementation on Cognitive Function in Athletes During a Fatiguing Cycling Exercise: A Randomized Cross-Over, Placebo-Controlled, and Double-Blind Study

Abstract: Background:Salvia (sage) supplementation has been shown to improve the cognition function in healthy individuals or patients (e.g., attention, memory). To date, no study has explored its relevancy in the context of sporting performance. The aim of this study was to explore the acute effects of a combination of Salvia officinalis and Salvia lavandulaefolia on cognitive function in athletes performing a fatiguing cycling task.Methods: Twenty-six volunteers were included in this cross-over, randomized, double-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Therefore, its inhibition leads to better symptoms and prognosis in Alzheimer’s [ 38 ]. Previous clinical studies showed that administration of sage oil and herbal teas improved mental and cognitive function in Alzheimer’s individuals [ 39 ]. Alcoholic extracts of S. officinalis exhibited in vitro inhibition of AChE and BChE, with higher inhibition observed against BChE [ 40 ], which is in accordance with the present results, but regarding the essential oil.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, its inhibition leads to better symptoms and prognosis in Alzheimer’s [ 38 ]. Previous clinical studies showed that administration of sage oil and herbal teas improved mental and cognitive function in Alzheimer’s individuals [ 39 ]. Alcoholic extracts of S. officinalis exhibited in vitro inhibition of AChE and BChE, with higher inhibition observed against BChE [ 40 ], which is in accordance with the present results, but regarding the essential oil.…”
Section: Resultsmentioning
confidence: 99%
“…This is due, specifically, to the inhibition of AChE, which is an enzyme that catalyzes the breakdown of acetylcholine. Using a combination of S. officinalis leaf extract mostly characterized for polyphenol content and S. lavandulaefolia EO with predominant terpenoids, a study observed improvements in memory and effects to Y-maze and Morris water maze markers on rodents in vivo [139][140][141]. This specific combination was also shown to be effective for the working memory accuracy of performance cognitive domains in healthy humans [142].…”
Section: Cognitive Effectsmentioning
confidence: 99%
“…6 In a recent randomized cross-over, placebo-controlled, and double-blind study, acute administration of Salvia mixture (400 mg of S. officinalis aqueous extract and 200 mg S. lavandulaefolia EO) encapsulated with acacia gum improved cognitive functions (perceived exertion, working memory, and reaction time) in athletes performing a fatiguing cycling task. 13…”
Section: Introductionmentioning
confidence: 99%
“…6 In a recent randomized cross-over, placebo-controlled, and double-blind study, acute administration of Salvia mixture (400 mg of S. officinalis aqueous extract and 200 mg S. lavandulaefolia EO) encapsulated with acacia gum improved cognitive functions (perceived exertion, working memory, and reaction time) in athletes performing a fatiguing cycling task. 13 There are great variations in the reported major components of S. lavandulifolia EO and their percentages in the literature, which can account for the variations in the biological activities of the EO. 1 These variations also suggest the presence of multiple chemotypes.…”
Section: Introductionmentioning
confidence: 99%